Depression in glioma: a primer for clinicians and researchers. Issue 2 (12th September 2013) - Rooney, Alasdair G; Brown, Paul D; Reijneveld, Jacob C; Grant, Robin
Abstract : Depression is one of the leading causes of global disability, and a considerable hidden morbidity among patients with glioma. In this narrative review, we summarise what is currently known about depression in glioma, the main unanswered questions and the types of studies that should be prioritised in order to find out. We conclude by calling for a prospective Phase II study of antidepressants in depressed glioma patients, to test methodologies for a multicentre randomised controlled trial.